Pemerolehan Kosakata Dalam Bahasa Jepang Melalui Pengajaran Bunpoo Dan Kaiwa - Made Ratna Dian Aryani (JLA (Jurnal Lingua Applicata), 2018)
The focus of this article is vocabulary acquisition of Japanese through demonstrative methods. This article is the result of research on the methods of vocabulary acquisition of Nursing Science students of Faculty of Medicine, Universitas Udayana. This article aims to explain the use of language teaching methods and strategies in non-language classes. The method used in this research is descriptive qualitative method. This article refers to the concept and theories formulated by Bandura (1986). Natural methods are used in learning Japanese grammar. Vocabulary acquisition can be obtained through the explanation of simple vocabularies that is started from a classroom environment, or through the dictionary used in the study. While, in conversation learning, the methods used are shadowing method and conversation method, which is supported by demonstrative strategies and the “question and answer” strategy. The strategy is employed by providing similar questions to all of the learners that make them try to look for different vocabularies to answer the question. The demonstrative strategy is used for observation, imitation and repetition, as well as development of the material of the context in real life situations.